Multifunctional conductive ink, preparation method thereof and application of multifunctional conductive ink in flexible transparent electrode

By adding analytical grade ethylene glycol and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide to PEDOT:PSS to form a continuous PEDOT conductive fiber network, the problems of low conductivity and poor printability of PEDOT:PSS conductive ink are solved, and a flexible transparent electrode with high conductivity and mechanical stability is achieved.

CN120795683APending Publication Date: 2025-10-17SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511037400.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing PEDOT:PSS conductive inks have low conductivity and poor printability. Ethylene glycol additives only provide limited improvement in conductivity and cannot meet both mechanical and process requirements.

Method used

Analytical grade ethylene glycol and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide are added to PEDOT:PSS. Through strong ion exchange and phase separation, a continuous PEDOT conductive fiber network is formed, optimizing the electron transport path and mechanical properties.

Benefits of technology

The conductive ink significantly improves conductivity and printability, exhibiting high conductivity and mechanical stability in flexible transparent electrodes, making it suitable for wearable electronic devices, flexible displays, and lighting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795683A_ABST
    Figure CN120795683A_ABST
Patent Text Reader

Abstract

The invention discloses multifunctional conductive ink, a preparation method thereof and application of the multifunctional conductive ink in a flexible transparent electrode. The conductive ink is prepared from the following components in parts by mass: PEDOT: 1 part of PSS, 0.05 part of analytically pure ethylene glycol and 0.005-0.01 part of 1-ethyl-3-methylimidazolium bis (trifluoromethanesulfonyl) imine. The preparation method comprises the following steps: under the condition of continuous stirring, adding treated analytically pure ethylene glycol and 1-ethyl-3-methylimidazolium bis (trifluoromethanesulfonyl) imine into an aqueous dispersion liquid of PEDOT: PSS, and carrying out ultrasonic dispersion to obtain the conductive ink; the conductive ink is used for preparing a large-area flexible transparent electrode, and the prepared electrode has high light transmittance and low sheet resistance. According to the invention, the problems of low conductivity and poor printability of the conductive ink taking PEDOT: PSS as a main body are solved. The conductive ink prepared by the invention can be widely applied to multiple fields of wearable electronic equipment, flexible display and illumination, health monitoring and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of conductive ink, and particularly relates to a multifunctional conductive ink, a preparation method thereof and application thereof in a flexible transparent electrode. BACKGROUND

[0002] Flexible transparent electrode (TCE) is widely used in touch interface, organic light emitting diode (OLED), interactive display, energy storage and energy harvesting, etc. due to its key role. For a long time, indium tin oxide (ITO) has been the mainstream TCE material due to its excellent photoelectric performance, i.e. high transparency and low sheet resistance. However, ITO has significant defects: its high-temperature vacuum deposition process limits its application on plastic substrates with poor heat resistance; its inherent brittleness makes it difficult to adapt to dynamic deformation scenarios; and the complex etching process not only easily causes circuit damage, but also leads to high processing cost. These limitations have prompted researchers to actively develop new transparent conductive materials that have excellent photoelectric properties and flexibility and reliability, among which metal nanomaterials, carbon nanotubes, graphene and conductive polymers have become research hotspots.

[0003] Poly(3,4-ethylenedioxythiophene) (PEDOT) is a conductive polymer with excellent performance. However, it is difficult to dissolve in most solvents itself, which brings many challenges to processing and handling. However, when it is combined with polystyrene sulfonic acid (PSS) to form a water-dispersible PEDOT:PSS composite, its solubility and dispersibility are greatly improved. This composite not only can stably exist in water and various polar organic solvents, but also can form a colloidal dispersion system with a core-shell structure, thereby significantly widening its application range. This good solution processability makes PEDOT:PSS suitable for low-cost, large-area preparation technologies such as spin coating and blade coating. However, its intrinsic conductivity is relatively low. Therefore, additives are often introduced for pretreatment or post-treatment to improve the conductivity. Commonly used additives include polar solvents, strong acids, surfactants or cross-linking agents. Weakly polar organic solvent ethylene glycol (EG) is often used as an additive, which can promote the phase separation of PEDOT and PSS, optimize the conductive channel, thereby improving the conductivity of the film and improving its wettability to the substrate. However, single EG only has limited gain on conductivity and cannot meet the mechanical and process requirements. SUMMARY

[0004] To overcome the shortcomings of the prior art, the purpose of the present application is to provide a multifunctional conductive ink, a preparation method thereof and application thereof in a flexible transparent electrode, which solves the problems of low conductivity and poor printing suitability of conductive ink based on PEDOT:PSS, and the addition of EG only has limited gain on conductivity.

[0005] The present application is realized by the following technical solutions:

[0006] A multifunctional conductive ink is composed of the following components in mass ratio: PEDOT: PSS 1 part, analytical pure ethylene glycol 0.05 part, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide 0.005-0.01 part.

[0007] Further, in the PEDOT: PSS, the mass ratio of PSS to PEDOT is 2.5:1.

[0008] A preparation method of a multifunctional conductive ink, comprising the following steps:

[0009] 1) The aqueous dispersion of PEDOT: PSS with a solid content of 1.3-1.5wt% is vacuum filtered through a 0.22-0.45μm PVDF filter membrane to remove >300nm aggregates;

[0010] 2) The analytical pure ethylene glycol is distilled under reduced pressure, and the fraction at 197-199℃ is collected, with the water content controlled to ≤50ppm; the treated analytical pure ethylene glycol is stored in a sealed bottle under inert gas protection;

[0011] 3) In an inert glove box with an oxygen content of less than 0.1ppm, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is mixed with activated molecular sieves calcined at 400-600℃ for 6-8 hours in a mass ratio of 1:5, and mechanically oscillated for 46-48 hours, then transferred through a 0.45μm PTFE needle filter for standby, wherein the water content of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is <15ppm;

[0012] 4) Under continuous stirring, the treated analytical pure ethylene glycol in step 2) and the treated 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide in step 3) are sequentially added to the aqueous dispersion of PEDOT: PSS treated in step 1) to obtain a mixed system;

[0013] 5) The mixed system is transferred into a titanium alloy probe ultrasonic reactor for ultrasonic dispersion, so that the agglomerates in the mixed system are dissociated to <50nm, and the temperature is controlled below 30℃ by ice bath;

[0014] 6) Under light shielding conditions, continuous stirring is carried out for 1-3h until a shear-thinning fluid state with a viscosity of 33-37mPa·s is reached, to obtain an ion liquid modified PEDOT: PSS conductive ink.

[0015] Further, the aqueous dispersion of PEDOT: PSS in step 1) is filtered through a three-stage gradient vacuum filtration system, with the initial pressure ≤5kPa, the final pressure ≤20kPa, and the third stage using a 0.22-0.45μm PVDF filter membrane.

[0016] Furthermore, the reduced pressure distillation in step 2) is specifically carried out in a reduced pressure distillation apparatus at 60° C. and 7.5-8.5 kPa.

[0017] Furthermore, the ultrasonic dispersion in step 5) is specifically performed by setting the amplitude to 39.5-40.5%, using a 5s ON / 2s OFF pulse sequence, and controlling the temperature in an ice bath circulation system to keep ΔT < 5°C / min for 20 minutes.

[0018] A multifunctional conductive ink is used in the preparation of a flexible transparent electrode, comprising the following steps:

[0019] a) Pre-treating the flexible material substrate and fixing the pre-treated flexible material on the device substrate:

[0020] b) injecting the conductive ink into a slit coating tool head at a speed of 5-10 μL / s;

[0021] c) performing slit coating on a flexible material substrate, controlling the coating gap to 1-20 μm and the coating speed to 5-10 mm / s;

[0022] d) After coating, gradient temperature annealing is performed under inert gas protection to obtain a flexible transparent electrode.

[0023] Furthermore, the flexible material substrate is plastic, and the pretreatment is specifically cleaning with detergent, deionized water, and isopropyl alcohol in sequence, drying with nitrogen, and then subjecting to oxygen plasma treatment at a power of 50-80 W for 60-150 s; the annealing in step d) is specifically maintaining at 80° C. for 5 minutes, then linearly increasing the temperature at 8° C. / min, maintaining at 120° C. for 10 minutes, and finally treating at 150° C. for 2 minutes.

[0024] Furthermore, the flexible material substrate is paper, and the pretreatment is specifically to use a solution of anhydrous ethanol and isopropyl alcohol mixed in a volume ratio of 1:1, wipe unidirectionally along the paper texture 2-3 times, and blow dry with 15L / min nitrogen; the annealing in step d) is specifically to keep warm at 80°C for 10 minutes and maintain at 100°C for 5 minutes, wherein the heating rate is 5°C / min.

[0025] Furthermore, the flexible transparent electrode has a transmittance in the visible light region greater than 80%; an electrical conductivity greater than 1,800 S / cm; a sheet resistance less than 100 Ω / sq; and a resistance change rate less than 5% after a bending cycle.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The application adds analytical pure ethylene glycol EG and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide EMIM-TFSI to PEDOT:PSS, the binding force of TFSI-anion of EMIM-TFSI and PEDOT + is significantly stronger than PSS - , thereby triggering strong ion exchange, so that the conductive PEDOT + is effectively dissociated and released; the addition of EG further induces the phase separation of PEDOT and PSS, promotes the π-π stacking of PEDOT, significantly shortens the electron transport path, and the conductivity is greatly improved; the strong ion exchange simultaneously induces the gelation of PEDOT:PSS, and the original core-shell micelle structure is transformed into a fiber network in situ, forming continuous PEDOT conductive fibers with a diameter of more than 300 nm. This structural evolution increases the viscosity of the system, endows the ink with excellent rheological adjustability, thereby significantly improving the printing resolution and film uniformity, and balancing high conductivity and large-scale printing suitability. The prepared conductive ink can be widely applied to wearable electronic devices, flexible display and lighting, health monitoring and other fields.

[0028] The preparation method of the conductive ink has the characteristics of simple preparation process and low cost.

[0029] The flexible transparent electrode prepared by the application has high conductivity (sheet resistance < 100 Ω / sq, electrical conductivity > 1,800 S / cm), high light transmittance (> 80%) in the visible light region, and excellent mechanical properties (resistance change rate < 5% after 1000 times of continuous bending with a bending radius of 5 mm). BRIEF DESCRIPTION OF DRAWINGS

[0030] Figure 1 The flow chart of the preparation method of the conductive ink of the application is shown in the figure;

[0031] Figure 2 The process schematic diagram of the preparation of the flexible transparent electrode of the application is shown in the figure;

[0032] Figure 3 The sample figure of the flexible transparent electrode prepared by the method of the application is shown in the figure;

[0033] Among them, 201 is an equipment substrate; 202 is a flexible material substrate; 203 is conductive ink; and 204 is a slot coating knife head. DETAILED DESCRIPTION

[0034] The application will be further described in detail below in combination with specific examples, which are an explanation of the application rather than a limitation.

[0035] A multifunctional conductive ink is composed of the following components in mass ratio: PEDOT:PSS 1 part, analytical pure ethylene glycol 0.05 part, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide 0.005-0.01 part; in the PEDOT:PSS, the mass ratio of PSS to PEDOT is 2.5:1.

[0036] As shown in Figure 1 A preparation method of a multifunctional conductive ink comprises the following steps:

[0037] 1) The aqueous dispersion of PEDOT:PSS with a solid content of 1.3-1.5wt% is vacuum filtered through a 0.22-0.45μm PVDF filter membrane to remove >300nm aggregates;

[0038] 2) The analytical pure ethylene glycol is distilled under reduced pressure, and the fraction at 197-199℃ is intercepted, with the water content controlled to ≤50ppm; the treated analytical pure ethylene glycol is stored in a sealed bottle under inert gas protection;

[0039] 3) In an inert glove box with an oxygen content of less than 0.1ppm, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is mixed with activated molecular sieves calcined at 400-600℃ for 6-8 hours at a mass ratio of 1:5, and after mechanical oscillation for 46-48 hours, it is transferred to a special storage tank through a 0.45μm PTFE needle filter, wherein the water content of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is <15ppm;

[0040] 4) Under continuous stirring, the treated analytical pure ethylene glycol in step 2) and the treated 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide in step 3) are added into the aqueous dispersion of PEDOT:PSS treated in step 1) in proportion, to obtain a mixed system, specifically:

[0041] In a 25℃ constant temperature water bath environment, EG is added dropwise into PEDOT:PSS at a mass ratio of PEDOT:PSS:EG=1:0.05 at 800rpm magnetic stirring (time-consuming 15±2min), EG is used to destroy the PSS insulating shell layer to induce PEDOT chain recombination; then EMIMTFSI is injected by a micro-injection pump (0.5mL / min) (ratio 1:0.005-0.01), to promote EMIM + insertion to reduce the π-π stacking distance; immediately perform probe sonication (amplitude 40%, pulse 5s / 2s) for 20min (ice bath temperature control <30℃), to use the cavitation effect to break the agglomerates;

[0042] 5) The mixed system was transferred to a titanium alloy probe ultrasonic reactor for ultrasonic dispersion to dissociate the agglomerates in the mixed system to less than 50 nm, and the temperature was controlled below 30° C. in an ice bath;

[0043] 6) Stirring was continued at 300 rpm for 1-3 h in a dark environment until a shear-thinning fluid state of 35±2 mPa·s was achieved, thereby forming an ionic liquid PEDOT:PSS core-shell structure and obtaining an ionic liquid-modified PEDOT:PSS conductive ink.

[0044] Example 1

[0045] A method for preparing a multifunctional conductive ink comprises the following steps:

[0046] Step 1: Clevios with a solid content of 1.3 wt% TM The PH1000 dispersion was filtered through a 0.22 μm PVDF membrane using a three-stage gradient vacuum filtration system (initial pressure ≤ 5 kPa, final pressure ≤ 20 kPa). After filtration, the unimodal particle size distribution was verified using a dynamic light scattering (DLS) instrument.

[0047] Step 2: Place analytical grade ethylene glycol in a 60°C / 7.5 kPa vacuum distillation apparatus, intercept the 197-199°C fraction, control the water content to ≤50 ppm by Karl Fischer titration, and store in a sealed ampoule under argon protection;

[0048] Step 3: In an inert glove box with an oxygen content of <0.1 ppm, EMIMTFSI was mixed with an activated carbon precipitate calcined at 400°C for 6 hours. The molecular sieves were mixed in a mass ratio of 1:5, mechanically shaken for 46 hours, and transferred to a dedicated storage tank through a 0.45 μm PTFE needle filter. The moisture content was <15 ppm.

[0049] Step 4. In a constant temperature water bath at 25.0±0.1°C, 1 g of PEDOT:PSS was placed in a three-necked flask, and 0.05 g of EG was precisely injected through a micro peristaltic pump (flow rate 0.2 mL / min), while maintaining magnetic stirring at 290 rpm to form a bicontinuous phase microstructure; 0.005 g of EMIMTFSI was injected using a Hamilton high-precision syringe pump (0.500±0.005 mL / min), and the conductive network formation was simultaneously monitored by a four-electrode in situ conductivity meter.

[0050] In step 5, the mixed system was immediately transferred to a titanium alloy probe ultrasonic reactor (Φ6 mm probe), the amplitude was set to 39.5%, a 5 s ON / 2 s OFF pulse sequence (duty cycle 70%) was used, the temperature was controlled below 30°C (ΔT < 5°C / min) by ice bath, and the dissociation of the agglomerates to < 50 nm was continued for 20 min.

[0051] Step 6: Mechanical stirring was continued at 295 rpm for 3 h in the dark, and the rheometer was used every 30 min (shear rate 100 s -1 ) The viscosity was monitored until a shear-thinning fluid state of 33 mPa·s (25°C) was reached.

[0052] Example 2

[0053] A method for preparing a multifunctional conductive ink comprises the following steps:

[0054] Step 1: Use Clevios with a solid content of 1.4 TM The PH1000 dispersion was filtered through a 0.35 μm PVDF membrane using a three-stage gradient vacuum filtration system (initial pressure ≤ 5 kPa, final pressure ≤ 20 kPa). After filtration, the unimodal particle size distribution was verified using a dynamic light scattering (DLS) instrument.

[0055] Step 2: Place analytical grade ethylene glycol in a 60°C / 8kPa vacuum distillation apparatus, intercept the 197-199°C fraction, control the water content to ≤50ppm by Karl Fischer titration, and store in a sealed ampoule under nitrogen protection;

[0056] Step 3: In an inert glove box with an oxygen content of <0.1 ppm, EMIMTFSI was mixed with an activated carbon precipitate calcined at 500°C for 7 hours. The molecular sieves were mixed in a mass ratio of 1:5, mechanically shaken for 47 hours, and transferred to a dedicated storage tank through a 0.45 μm PTFE needle filter. The moisture content was <15 ppm.

[0057] Step 4. In a constant temperature water bath at 25.0±0.1°C, 1 g of PEDOT:PSS was placed in a three-necked flask, and 0.05 g of EG was precisely injected through a microperistaltic pump (flow rate 0.2 mL / min), while maintaining magnetic stirring at 300 rpm to form a bicontinuous phase microstructure; 0.0075 g of EMIMTFSI was injected using a Hamilton high-precision syringe pump (0.500±0.005 mL / min), and the conductive network formation was simultaneously monitored by a four-electrode in situ conductivity meter.

[0058] In step 5, the mixed system was immediately transferred to a titanium alloy probe ultrasonic reactor (Φ6 mm probe), the amplitude was set to 40.0%, a 5 s ON / 2 s OFF pulse sequence (duty cycle 70%) was used, the temperature was controlled below 30°C (ΔT < 5°C / min) by ice bath, and the dissociation of the agglomerates to < 50 nm was continued for 20 min.

[0059] Step 6: Mechanical stirring was continued at 300 rpm for 1 h in the dark, and the mixture was measured every 30 min using a cone-plate rheometer (shear rate 100 s -1) The viscosity was monitored until a shear-thinning fluid state of 35.0 mPa·s (25° C.) was reached.

[0060] Example 3

[0061] A method for preparing a multifunctional conductive ink comprises the following steps:

[0062] Step 1: Clevios with a solid content of 1.5 wt% TM The PH1000 dispersion was filtered through a 0.45 μm PVDF membrane using a three-stage gradient vacuum filtration system (initial pressure ≤ 5 kPa, final pressure ≤ 20 kPa). After filtration, the unimodal particle size distribution was verified using a dynamic light scattering (DLS) instrument.

[0063] Step 2: Place analytical grade ethylene glycol in a 60°C / 8.5 kPa vacuum distillation apparatus, intercept the 197-199°C fraction, control the water content to ≤50 ppm by Karl Fischer titration, and store in a sealed ampoule under helium protection;

[0064] Step 3: In an inert glove box with an oxygen content of <0.1 ppm, EMIMTFSI was mixed with an activated carbon precipitate calcined at 600°C for 8 hours. The molecular sieves were mixed in a mass ratio of 1:5, mechanically shaken for 48 hours, and transferred to a dedicated storage tank through a 0.45 μm PTFE needle filter. The moisture content was <15 ppm.

[0065] Step 4: In a constant temperature water bath at 25.0±0.1°C, 1 g of PEDOT:PSS was placed in a three-necked flask, and 0.05 g of EG was precisely injected through a micro peristaltic pump (flow rate 0.2 mL / min), and magnetic stirring was maintained at 300±10 rpm to form a bicontinuous phase microstructure; 0.01 g of EMIMTFSI was injected using a Hamilton high-precision syringe pump (0.500±0.005 mL / min), and the conductive network formation was simultaneously monitored by a four-electrode in situ conductivity meter.

[0066] In step 5, the mixed system was immediately transferred to a titanium alloy probe ultrasonic reactor (Φ6 mm probe), the amplitude was set to 40.5%, a 5 s ON / 2 s OFF pulse sequence (duty cycle 70%) was used, the temperature was controlled below 30°C (ΔT < 5°C / min) by ice bath, and the dissociation of the agglomerates to < 50 nm was continued for 20 min.

[0067] Step 6: Mechanical stirring was continued at 305 rpm for 3 h in the dark, and the rheometer was used every 30 min (shear rate 100 s -1 ) The viscosity was monitored until a shear-thinning fluid state of 37 mPa·s (25°C) was reached.

[0068] likeFigure 2 The conductive graphite prepared by the application is used for preparing a flexible transparent electrode by slit coating.

[0069] Example 4

[0070] The application of a multifunctional conductive ink in the preparation of a flexible transparent electrode comprises the following steps:

[0071] a) The 0.1 mm PET flexible material substrate 202 is sequentially cleaned with a decontaminating agent, deionized water, and isopropyl alcohol, and after being dried with nitrogen, is placed in a radio frequency plasma chamber for oxygen plasma treatment at a power of 50 W for 150 s, with an O flow rate of 50 sccm, and the water contact angle is verified by a contact angle tester to be 78°→22°, and the pretreated flexible material is fixed on the equipment substrate 201;

[0072] b) The conductive ink 203 is injected into the slit coating knife head 204, and the ink injection speed is set to 5 μL / s;

[0073] c) In a Class 1000 clean room (temperature 23±2℃, RH 30.0±0.5%), a laser displacement sensor is used to calibrate the coating gap to 1 μm in real time, an infrared focal plane array is used to control the substrate temperature to 80.0℃, and a servo motor is used to drive the coating speed to 5 mm / s to activate the shear thinning effect; a gear pump with a precision of ±0.25% is used to deliver the ink to the coating knife head 204, and a uniform wet film with a thickness of 11.5 μm is formed on the flexible material substrate 202, with an edge undulation of <0.5 μm;

[0074] d) Three-stage annealing is performed in a nitrogen protection cabinet (oxygen content ≤5 ppm): 80℃ for 5 min to induce solvent evaporation, linear heating to 120℃ at a rate of 8℃ / min for 10 min to promote PEDOT crystallization, and a stepwise increase in temperature to 150℃ for 2 min to eliminate interface defects, and a synchronous four-probe system is used to monitor the resistance drop.

[0075] Example 5

[0076] The application of a multifunctional conductive ink in the preparation of a flexible transparent electrode comprises the following steps:

[0077] a) The 0.1 mm PET flexible material substrate 202 is sequentially cleaned with a decontaminating agent, deionized water, and isopropyl alcohol, and after being dried with nitrogen, is placed in a radio frequency plasma chamber for oxygen plasma treatment at a power of 80 W for 60 s, with an O flow rate of 50 sccm, and the water contact angle is verified by a contact angle tester to be 78°→22°, and the pretreated flexible material is fixed on the equipment substrate 201;

[0078] b) The conductive ink 203 is injected into the slit coating knife head 204, and the ink injection speed is set to 10 μL / s;

[0079] c) In a Class 1000 clean room (temperature 23±2°C, RH 30.0±0.5%), the coating gap is calibrated to 20 μm in real time using a laser displacement sensor, the substrate temperature is controlled at 80.5°C using an infrared focal plane array, and the coating speed is 10 mm / s using a servo motor to activate the shear thinning effect; the ink is delivered to the coating knife head 204 through a gear pump with a precision of ±0.25%, and a uniform wet film with a thickness of 12.5 μm is formed on the flexible material substrate 202, with an edge undulation of <0.5 μm;

[0080] d) The three-stage annealing is performed in a nitrogen protection cabinet (oxygen content ≤5 ppm): 80°C for 5 min to induce solvent evaporation, linear heating to 120°C at a rate of 8°C / min for 10 min to promote PEDOT crystallization, and a step increase to 150°C for 2 min to eliminate interface defects, with a synchronous four-probe system monitoring the resistance drop.

[0081] Example 6

[0082] The application of a multifunctional conductive ink in the preparation of a flexible transparent electrode includes the following steps:

[0083] a) The flexible material substrate 202 is pretreated by wiping it twice with a 0.3 μm pore size ultrafine fiber cloth dipped in a solution of anhydrous ethanol and isopropyl alcohol mixed at a volume ratio of 1:1 along the paper texture, removing >99% of surface contaminants; the surface residual solvent is <0.1 μg / cm using a 45° inclined nitrogen gun (flow rate 15 L / min, distance 3 cm) to blow off; 2 The pretreated flexible material is fixed on the equipment substrate 201;

[0084] b) The conductive ink 203 is injected into the slot coating knife head 204, and the ink injection speed is set to 7 μL / s;

[0085] c) In a Class 1000 clean room (temperature 23±2°C, RH 30.0±0.5%), the coating gap is calibrated to 10 μm in real time using a laser displacement sensor; the coating speed is 6 mm / s to prevent shear force from damaging the fiber structure; the substrate temperature is controlled at 60°C to avoid cellulose pyrolysis;

[0086] d) Under the protection of inert gas, gradient temperature annealing is performed at 80°C for 10 min and 100°C for 5 min, with a heating rate of 5°C / min to prevent paper scorching under nitrogen protection.

[0087] Example 7

[0088] The application of a multifunctional conductive ink in the preparation of a flexible transparent electrode includes the following steps:

[0089] a) The flexible material substrate 202 is pretreated by wiping 3 times along the paper texture in one direction using a 0.3 μm pore size ultra-fine fiber cloth dipped in a solution of anhydrous ethanol and isopropyl alcohol mixed at a volume ratio of 1:1, removing >99% of surface contaminants; the surface residual solvent is <0.1 μg / cm2 using a 45° angle nitrogen gun (flow rate 15 L / min, distance 3 cm) to blow off 2 The pretreated flexible material is fixed on the device substrate 201;

[0090] b) The conductive ink 203 is injected into the slot coater knife head 204, and the ink injection speed is set to 8 μL / s;

[0091] c) In a Class 1000 clean room (temperature 23±2℃, RH 30.0±0.5%), the coating gap is calibrated to 15 μm in real time using a laser displacement sensor; the coating speed is 8 mm / s to prevent shear force from destroying the fiber structure; the substrate temperature is controlled at 61℃ to avoid cellulose pyrolysis;

[0092] d) Gradient temperature annealing is performed under inert gas protection at 80℃ for 10 min and 100℃ for 5 min, wherein the heating rate is 5℃ / min, and nitrogen protection is used to prevent paper charring.

[0093] As shown in FIG. 1, the flexible transparent electrode prepared in the present application has high transparency. Figure 3

[0094] The present application introduces ionic liquids (ILs) as a key progressive, and the ILs have a dual identity of "conductive enhancer + plasticizer": the anion of the ILs is similar to the anion of the PEDOT + ​High efficient ion exchange occurs, which drives PEDOT chain segment conformation to relax and arrange orderly, and regulates PSS phase, cooperates with phase separation induced by EG to realize double optimization of electronic channel and mechanical network; at the same time, ILs triggered gelation significantly increases the viscosity of the system, so that the composite ink has excellent flexibility and printability. EG dominates phase separation, and IL is responsible for ion exchange - both of which cooperatively build PEDOT:PSS / IL composite materials with excellent electrical and mechanical properties, perfectly matching compatible processes such as screen printing, gravure printing and slot-die coating. Slot-die coating, as an efficient and scalable large-area solution processing technology, can accurately control the film thickness and uniformity, and is an ideal choice for realizing low-cost, roll-to-roll production of high-performance TCE. Benefiting from the excellent processability and rheological properties of the PEDOT:PSS / IL composite system, the electrode film prepared by slot-die coating exhibits high transparency and low sheet resistance, while maintaining excellent flexibility and mechanical stability. This high-performance large-area flexible transparent electrode has broad market application prospects in the fields of wearable electronic devices, flexible display and lighting, advanced medical devices and health monitoring, etc.

[0095] The above examples are only used to illustrate the technical solutions of the present application, but not to limit it. Although the present application has been described in detail with reference to the above examples, those skilled in the art should understand that the specific embodiments of the present application can still be adjusted or replaced equivalently. Any modification or equivalent replacement without departing from the spirit and scope of the present application should be covered within the scope of the claims of the present patent.

Claims

1. A multifunctional conductive ink, characterized in that: The preparation method comprises the following components in a mass ratio: 1 part of PEDOT:PS S, 0.05 part of analytical grade ethylene glycol, and 0.005-0.01 part of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.

2. The multifunctional conductive ink according to claim 1, characterized in that: In the PEDOT:PSS, the mass ratio of PSS to PEDOT is 2.5:

1.

3. A method for preparing the multifunctional conductive ink according to claim 1 or 2, characterized in that: The following steps are involved: 1) Vacuum filtration of an aqueous dispersion of PEDOT:PSS with a solid content of 1.3-1.5 wt% through a 0.22-0.45 μm PVDF filter membrane to remove aggregates larger than 300 nm; 2) Distill the analytically pure ethylene glycol under reduced pressure, intercept the 197-199°C fraction, control the water content to ≤50ppm, and store the treated analytically pure ethylene glycol in a sealed bottle under inert gas protection; 3) In an inert glove box with an oxygen content of less than 0.1 ppm, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide was reacted with an activated catalyst calcined at 400-600°C for 6-8 hours. The molecular sieves were mixed at a mass ratio of 1:5, mechanically shaken for 46-48 hours, and then transferred through a 0.45 μm PTFE syringe filter for use. The moisture content of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide was <15 ppm; 4) under continuous stirring, adding the analytically pure ethylene glycol treated in step 2) and the 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide treated in step 3) to the aqueous dispersion of PEDO T:PSS treated in step 1) in proportion to obtain a mixed system; 5) The mixed system was transferred to a titanium alloy probe ultrasonic reactor for ultrasonic dispersion to dissociate the agglomerates in the mixed system to less than 50 nm, and the temperature was controlled below 30° C. in an ice bath; 6) Stirring was continued for 1-3 hours in a dark environment until a shear-thinning fluid state of 33-37 mPa·s was achieved to obtain an ionic liquid-modified PEDOT:PSS conductive ink.

4. The method for preparing the multifunctional conductive ink according to claim 3, wherein: In step 1), the aqueous dispersion of PEDOT:PSS is filtered through a three-stage gradient vacuum filtration system with an initial pressure of ≤5 kPa and a final pressure of ≤20 kPa, and a 0.22-0.45 μm PVDF filter membrane is used in the third stage.

5. The method for preparing the multifunctional conductive ink according to claim 3, wherein: The reduced pressure distillation in step 2) is specifically carried out in a reduced pressure distillation apparatus at 60° C. and 7.5-8.5 kPa.

6. The method for preparing the multifunctional conductive ink according to claim 3, wherein: In step 5), the ultrasonic dispersion is specifically performed by setting the amplitude to 39.5-40.5%, using a 5s ON / 2s OFF pulse sequence, and controlling the temperature in an ice bath circulation system to keep ΔT < 5°C / min for 20 minutes.

7. Use of the multifunctional conductive ink according to claim 1 or 2 in the preparation of a flexible transparent electrode, characterized in that: The following steps are involved: a) pre-treating the flexible material substrate (202) and fixing the pre-treated flexible material on the device substrate (201): b) injecting the conductive ink (203) into the slit coating blade (204) at an ink injection speed of 5-10 μL / s; c) performing slit coating on the flexible material substrate (202), controlling the coating gap to be 1-20 μm and the coating speed to be 5-10 mm / s; d) After coating, gradient temperature annealing is performed under inert gas protection to obtain a flexible transparent electrode.

8. The use of the multifunctional conductive ink in the preparation of a flexible transparent electrode according to claim 7, characterized in that: The flexible material substrate (202) is plastic, and the pretreatment specifically includes cleaning with a detergent, deionized water, and isopropyl alcohol in sequence, drying with nitrogen, and then subjecting to oxygen plasma treatment at a power of 50-80W for 60-150s; the annealing in the step d) specifically includes keeping the temperature at 80°C for 5 minutes, linearly increasing the temperature at 8°C / min, maintaining the temperature at 120°C for 10 minutes, and finally treating the temperature at 150°C for 2 minutes.

9. The use of the multifunctional conductive ink in the preparation of a flexible transparent electrode according to claim 7, characterized in that: The flexible material substrate (202) is paper, and the pretreatment specifically comprises using a solution of anhydrous ethanol and isopropyl alcohol mixed in a volume ratio of 1:1, wiping the paper in one direction along the paper texture for 2-3 times, and blowing it dry with 15L / min nitrogen; the annealing in the step d) specifically comprises keeping the temperature at 80°C for 10 minutes and maintaining the temperature at 100°C for 5 minutes, wherein the heating rate is 5°C / min.

10. The use of the multifunctional conductive ink in the preparation of a flexible transparent electrode according to claim 7, characterized in that: The flexible transparent electrode has a visible light transmittance of >80%; an electrical conductivity of >1,800 S / cm; a sheet resistance of <100 Ω / sq; and a resistance change rate of <5% after a bending cycle.